An investigation into the community health survey 2019 to analyze the health-related quality of life - Hong, Jeongju; Kim, Jae-Hee (Edelweiss Applied Science and Technology, 2025)
This study aimed to investigate the factors influencing health-related quality of life (HRQoL) among Korean adults using data from the 2019 Community Health Survey (CHS). A cross-sectional analysis was performed utilizing a nationally representative dataset. HRQoL was measured through the EuroQol-5 Dimension (EQ-5D) instrument. Descriptive statistics, t-tests, analysis of variance (ANOVA), and multiple regression analyses were conducted to examine the associations between HRQoL and various demographic and behavioral variables. The findings revealed that age, gender, educational attainment, and household income were significantly associated with HRQoL. Furthermore, health behaviors, including smoking, alcohol consumption, and physical activity, exhibited substantial impacts on HRQoL. These results underscore the necessity of developing tailored public health interventions that address both sociodemographic and behavioral determinants to enhance population health outcomes. The study offers practical implications for policymakers and healthcare professionals in formulating effective strategies aimed at improving quality of life across diverse demographic groups.